Plica Neuropathica as a Presenting Rare Dermatologic Symptom of Schizophrenia - Piyanonpong W; Suchonwanit P (Dove Medical Press, 2023)
Waritsara Piyanonpong, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat Suchonwanit, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211 Ext 4, Email poonkiat@hotmail.comAbstract: Plica neuropathica (PN), also known as plica polonica, trichoma, matting, felting, or bird's nest hair, is a common but rarely reported hair disorder. It is characterized by the abrupt onset of irreversible hair entanglement, forming a densely matted hair mass. PN has been associated with the use of ionic or herbal shampoos, vigorous hair care practice, self-neglect, systemic infection, parasitic infestation, immunosuppressive drugs, and psychiatric conditions. However, literature supporting the coexistence of PN in psychiatric disorders is scarce. PN may be one of the presenting symptoms observed by physicians. In some cases of psychiatric illness, patients consult more readily with non-mental health professionals than psychologists or psychiatrists. To highlight this issue, we herein report a case of PN in a 32-year-old woman with a 1-month history of being unable to detangle her hair. The patient initially visited the dermatology department and was subsequently diagnosed with schizophrenia following psychiatric consultation. After establishing the fundamental diagnosis apparently underlying the PN, psychiatric treatment with antipsychotic medication and dermatological treatment of the hair condition were instituted. There was an improvement in both at the four-week follow-up. This case history highlights a rare presentation of schizophrenia.Keywords: electrostatic force, hair care, matted hair, psychodermatology, self-neglect, trichology